Clinical implications of T cell exhaustion for cancer immunotherapy - Chow, Andrew; Perica, Karlo; Klebanoff, Christopher A; Wolchok, Jedd D (Nature reviews. Clinical oncology, 2022)
Immunotherapy has been a remarkable clinical advancement in the treatment of cancer. T cells are pivotal to the efficacy of current cancer immunotherapies, including immune-checkpoint inhibitors and adoptive cell therapies. However, cancer is associated with T cell exhaustion, a hypofunctional state characterized by progressive loss of T cell effector functions and self-renewal capacity. The 'un-exhausting' of T cells in the tumour microenvironment is commonly regarded as a key mechanism of action for immune-checkpoint inhibitors, and T cell exhaustion is considered a pathway of resistance for cellular immunotherapies. Several elegant studies have provided important insights into the transcriptional and epigenetic programmes that govern T cell exhaustion. In this Review, we highlight recent discoveries related to the immunobiology of T cell exhaustion that offer a more nuanced perspective beyond this hypofunctional state being entirely undesirable. We review evidence that T cell exhaustion might be as much a reflection as it is the cause of poor tumour control. Furthermore, we hypothesize that, in certain contexts of chronic antigen stimulation, interruption of the exhaustion programme might impair T cell persistence. Therefore, the prioritization of interventions that mitigate the development of T cell exhaustion, including orthogonal cytoreduction therapies and novel cellular engineering strategies, might ultimately confer superior clinical outcomes and the greatest advances in cancer immunotherapy.